Didactics of translation for future opera singers - Štroblová, Kateřina (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
Future opera singers study Italian as a foreign language, but they also need translation activities to understand deeply the lyric texts that they interpret. This article describes the teaching practices used at the Conservatory of Pilsen in the Czech Republic, analyses aspects that distinguish operatic language from ordinary language, and presents research conducted with the aim of comparing the lexical knowledge obtained as a benefit of generic language courses and the specific knowledge required for the translation of lyric texts.